A concept of critical safety area applicable for an obstacle-avoidance process for manned and autonomous ships. (October 2021) - Gil, Mateusz
Highlights: Improved version of the Collision Avoidance Dynamic Critical Area (CADCA) is proposed for ship encounters with stationary obstacles The CADCA concept has been improved to increase its accuracy and computation time Modern cruise ship and post-Panamax container vessel are utilized in the simulation study Encounters with four obstacles differing in size and shape are investigated The impact of ship operational parameters on the required maneuvering area (rudder angle, initial speed, course alteration) is investigated Abstract: In times of increased automation of maritime transportation, ship collision with a stationary obstacle (allision) remains a significant problem. There are many existing solutions rooted primarily in the concept of ship domain and path-planning algorithms. However, among these, a geometrical approach to the determination of a required maneuvering area considering the dynamic nature of ship operations in close-quarters situations is still missing. Therefore, an improved concept of the CADCA ( Collision Avoidance Dynamic Critical Area ) is introduced for the case of ship allision. The CADCA is a deterministic zone that geometrically delimits required maneuvering space of a vessel. Its shape changes depending on the operational parameters of a ship, such as the magnitude of rudder angle, initial forward speed, or planned alteration of the course. In contrast to ship domain, the CADCA is determined using the critical distance between two objects called MDTC ( Minimum Distance to Collision ). Therefore, the CADCA concept can be used to appoint a position of no-return in a close-quarters situation, so as to determine the time and distance of the last-minute maneuver. An improved method of CADCA determination is introduced, along with an investigation of operational factors influencing the ship's critical area in allision scenarios. The simulations have been conducted for large passenger and container ship in encounters with various stationary obstacles differing in size and shape. The results indicate that from the operational point of view, a deflection of the rudder is the most influencing factor on the size of the CADCA, while the impact of ship speed is negligible for the investigated vessels. Besides, various applications of the CADCA are proposed and discussed for both manned and prospective autonomous vessels.